A Translation Study on Responding of Requesting Speech Act in The Novel The Heroes of Olympus Series - dewinta khoirul anis (IAIN Salatiga, 2017)
This research discusses about the types of responding of requesting speech act used in the novel the Heroes of Olympus Series, describes the translation techniques usage and assess the translation quality in terms of acceptability. This research can be classified as a descriptive qualitative research which focuses on a single case. The source data of this research are the documents and persons, i.e. the novel The Heroes of Olympus series and those called raters who have competencies in assessing translation quality. The methods to collect and analyze the data of responding of requesting speech act were applied content analysis and Forum Group Discussion. The result of this research shows the discovery of 11 types of responding of requesting speech act such as agreeing, commenting, informing, explaining, committing, etc. Based on the techniques that are proposed by Molina Albir (2002), there are 17 translation techniques found in this research, which is, from the analysis of 89 data of responding of requesting speech act in source text and target text, found 564 times the use of its translation techniques. And, in general, the resulting of translation quality in the form of acceptability assessment in this study tends to be good because the average is 2.86, with the majority of applying Establish equivalent technique that gives a positive impact on the translation quality.